THE IMPACT OF WORK DISCIPLINE AND MOTIVATION ON EMPLOYEE PRODUCTIVITY: THE MEDIATING ROLE OF JOB SATISFACTION - Yuanis Yuanis; Salsabila Firdausya (J-MACC, 2026)
Employee productivity in the regional water distribution sector is often constrained by low work discipline and uneven motivation, while the mediating role of job satisfaction remains underexplored. This study examines the mediating effect of job satisfaction on the relationship between work discipline, motivation, and employee productivity at PDAM Tirta, Indonesia. A quantitative cross-sectional design was employed, involving 182 employees selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire with high reliability (Cronbach’s Alpha = 0.887–0.918) and analyzed using path analysis, Sobel test, and bootstrapping. The results indicate that work discipline (β = 0.287) and motivation (β = 0.315) significantly affect productivity, while job satisfaction is the strongest predictor (β = 0.348). Job satisfaction also partially mediates the relationships between work discipline and productivity, and between motivation and productivity. These findings highlight the central role of job satisfaction in enhancing employee productivity.